The 2020 US Presidential Election and Trump's Trade War - James Lake; Jun Nie (Center for Economic Studies and ifo Institute (CESifo), 2022)
The trade war initiated by the Trump administration is the largest since the US imposed the Smoot-Hawley tariffs in the 1930s and was still raging when he left office. We analyze how the trade war impacted the 2020 US Presidential election. Our results highlight the political salience of the trade war: US trade war tariffs boosted Trump's support but foreign retaliation hurt Trump. In particular, the pro-Trump effects of US trade war tariffs were crucial for Trump crossing the recount thresholds in Georgia and Wisconsin. These effects cross political and racial lines, suggesting the mechanism operates through the impact on local economies rather than political polarization. Even more important politically, voters abandoned Trump in counties with large expansions of health insurance coverage since the Affordable Care Act, presumably fearing the roll-back of such expansion. Absent this anti-Trump effect, Trump would have been on the precipice of re-election by winning Georgia, Arizona, Nevada, and only losing Wisconsin by a few thousand votes.
Keywords: D72; F13; F14; I18; 330; 2020 US Presidential election; Trump; Affordable Care Act; health insurance; trade war; tariffs; retaliation